PELATIHAN MENGGAMBAR BERTEMA DI SD N 3 BANJARANGKAN, KABUPATEN KLUNGKUNG - I Wayan Arissusila; I Ketut Suwidiarta; I Ketut Gede Rudita (JURNAL SEWAKA BHAKTI, 2020)
Education through the drawing method is considered very important because the benchmarks of students’ success are not only assessed from general lessons, but students’ interest in a particular field is also important, for example drawing. Themed drawing training at SDN 3 Banjarangkan, using dry media in the form of colored pencils and crayons that are sketched on drawing paper, with the theme of daily life, the surrounding environment and others. The purpose of themed drawing training is to liberate imagination and character development. The process that students go through in this themed drawing is: learning theories about basic drawing, for example making lines, shapes, coloring, dark light and others. Then sketching, contouring, coloring and making textures. The results obtained in the form of pictures with natural shapes in the surrounding environment and their contents. The purpose of this themed drawing training is to train students' abilities quickly, creativity, release of imagination and character development.